Social tensions in enterprises: the theoretical and methodological aspect of analysis - Андрющенко, А. І.; Євдокимова, І. А. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2019)
The article is devoted to the theoretical aspects of analysis of social-labor relations in the organizations. As an indicator of last one is the level of social tension. Authors analyze the level of social tension on the latent stage that allow to develop measures to resolve social conflicts.